Анализ вынужденных колебаний системы с двумя степенями свободы, содержащей существенно нелинейный виброгаситель - Решетникова, Светлана Николаевна; Галас, Олег Сергеевич (НТУ "ХПИ", 2003)
Concept of nonlinear normal modes is used to study vibrations of some elastic structures attached with single-DOF nonlinear elastic absorbers. The localized vibration modes favorable for the absorption are allocated. Stability of nonlocalized modes is investigated. The forced vibrations in such systems are considered also, the principal resonances are analyzed. Forced resonances of the systems under consideration are considered too
Keywords: упругие виброгасители; виброзащита; осциллятор; устойчивость вынужденных колебаний; затухающие вынужденные колебания